Integrative approach in the study of ethnic (national) identity concept - Dossova, N S; Kambarov B.K., K B; Mukatova А М (Journal of Oriental Studies, 2016)
The article is dedicated to the study of identity, ethnic (national) identity in the modern world. The need for an integrative approach based on a combination of private approaches is shown on the analysis of the main approaches to the study of ethnic identity.